Barriers to the practice of physical activity and stage of behavior change in employees of a teaching hospital in southern Brazil (Research, Society and Development, 2021)
This study aimed to analyze the association of self-reported barriers to the practice of physical activity and stage of behavior change in employees of a Teaching Hospital in southern Brazil. Cross-sectional study, which investigated 485 workers at a Teaching Hospital in southern Brazil, 313 women and 172 men. The variables analyzed were: level of physical activity, body mass index, waist circumference, age, smoking, alcohol consumption, hours spent sleeping, stage of behavior change and barriers to physical activity. Descriptive statistics were used in median, minimum and maximum values ​​to characterize the population, in addition to using the Mann-Whitney U test for comparison between genders. The Chi-square test (p